Trinidad, Blue Basin - Briant (Davidson and Todd, [Trinidad and Tobago], 2011)
The postcard shows the magnificent Blue Basin Waterfall located in Diego Martin, a town located in the northwest of Trinidad.
Colour: Sepia with hues of green; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Diego Martin; Waterfalls